SIRT3 Is a Critical Regulator of Mitochondrial Function of Fibroblasts in Pulmonary Hypertension - Li, Min; Plecitá-Hlavatá, Lydie; Dobrinskikh, Evgenia; McKeon, B Alexandre; Gandjeva, Aneta; Riddle, Suzette; Laux, Aya; Prasad, Ram Raj; Kumar, Sushil; Tuder, Rubin M; Zhang, Hui; Hu, Cheng-Jun; et al. (American journal of respiratory cell and molecular biology, 2023)
Pulmonary hypertension (PH) is a heterogeneous and life-threatening cardiopulmonary disorder in which mitochondrial dysfunction is believed to drive pathogenesis, although the underlying mechanisms remain unclear. To determine if abnormal SIRT3 (sirtuin 3) activity is related to mitochondrial dysfunction in adventitial fibroblasts from patients with idiopathic pulmonary arterial hypertension (IPAH) and hypoxic PH calves (PH-Fibs) and whether SIRT3 could be a potential therapeutic target to improve mitochondrial function, SIRT3 concentrations in control fibroblasts, PH-Fibs, and lung tissues were determined using quantitative real-time PCR and western blot. SIRT3 deacetylase activity in cells and lung tissues was determined using western blot, immunohistochemistry staining, and immunoprecipitation. Glycolysis and mitochondrial function in fibroblasts were measured using respiratory analysis and fluorescence-lifetime imaging microscopy. The effects of restoring SIRT3 activity (by overexpression of SIRT3 with plasmid, activation SIRT3 with honokiol, and supplementation with the SIRT3 cofactor nicotinamide adenine dinucleotide [NAD+]) on mitochondrial protein acetylation, mitochondrial function, cell proliferation, and gene expression in PH-Fibs were also investigated. We found that SIRT3 concentrations were decreased in PH-Fibs and PH lung tissues, and its cofactor, NAD+, was also decreased in PH-Fibs. Increased acetylation in overall mitochondrial proteins and SIRT3-specific targets (MPC1 [mitochondrial pyruvate carrier 1] and MnSOD2 [mitochondrial superoxide dismutase]), as well as decreased MnSOD2 activity, was identified in PH-Fibs and PH lung tissues. Normalization of SIRT3 activity, by increasing its expression with plasmid or with honokiol and supplementation with its cofactor NAD+, reduced mitochondrial protein acetylation, improved mitochondrial function, inhibited proliferation, and induced apoptosis in PH-Fibs. Thus, our study demonstrated that restoration of SIRT3 activity in PH-Fibs can reduce mitochondrial protein acetylation and restore mitochondrial function and PH-Fib phenotype in PH.
Keywords: Cattle; Animals; skot; Hypertension, Pulmonary; Mitochondria; SIRT3; Fibroblasts; honokiol; pulmonary hypertension; lidé; nicotinamide adenine dinucleotide; NAD; mitochondria; mitochondriální proteiny; fibroblasty; mitochondrie; plicní hypertenze; sirtuin 3; Mitochondrial Proteins; zvířata; Sirtuin 3; Humans